The block wave region growing of the image based on quadra-grid pixels - O. M. Almiahi; V. YU. Tsviatkou; V. K. Kanapelka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Algorithms for fast segmentation of gray scale images based on the block of the wave region growing using quadra-grid pixels are suggested. The algorithms allow to adapt to accessible computational resources and the required accuracy of the segmentation through choosing quadra-grid step.